Cervical cancer screening guidelines: An update. Issue 9 (September 2021) - Shami, Sarah; Coombs, Jennifer
Abstract : ABSTRACT: Cervical cancer screening practices in the United States have been inefficient, with variable screening rates. Some women are screened too frequently, overmanaged, lost to follow-up, or are at risk and should be screened but are not. Timely screening, identification, and management of abnormal cervical cells is vital in order to prevent progression to cervical cancer. Educating, counseling, screening, and offering the human papillomavirus vaccine continue to be the primary methods of cervical cancer prevention practices. Guidelines and primary screening methods have been updated because of supporting evidence, and clinicians must stay up-to-date in order to provide effective patient care.